Analysis of the Development of Falsafi Tafsir in Islamic Perspective - Lusianasta Mandini Hermanto Putri; Af'roh Af'roh; Khoirul Hanifah (Al-Shamela : Journal of Quranic and Hadith Studies, 2025)
The Qur'an has proven its miracle, not only in terms of its existence but also in its teachings that have been proven by its development. The existence of tafsir cannot be separated from the interaction between the Islamic world and Greek philosophical thought. This article aims to analyze the development of falsafi tafsir, where the emergence of this tafsir in medieval times has contributed to the development of Qur'anic tafsir. The method used is qualitative with a descriptive analytical approach. Primary data obtained from various literature on falsafi tafsir, while secondary data as supporting documents, such as books, journals, and articles. Thus, the results show that the existence of interpretation with a falsafi tafsir style has become a new color in the method of interpreting the Qur'an, namely with a hermeneutic approach. This falsafi tafsir has contributed a lot to thought in the Islamic world, not only understanding in terms of the word and context of God, but also changing human perceptions for the better.